Mutual Interests of Literary Criticism and Musical Criticism in the Field of Written Works A Case Study: "Music of Poetry" and "The Association of Poetry and Music" - Hamid Askari Rabori (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The association between Literature and Music is represented mostly in Vocal Music and the music of poetry. It is notable that the new compiled written works in the literary-musical field of “poetry and vocal music association” has encountered new issues rather than finding equivalence for metric and rhythmic prosodic meters of Persian poetry which literary criticism has remained far from studying them. On the other hand, in recent decades, “Music of Poetry” concept with the formalist theme has suggested aesthetical criteria in studying and criticizing Persian poetry, and it has benefited from musical terms such as musicality, harmony, orchestration, etc. while musical critique has not presented any comment on written works of "music of poetry". Complexity and scarcity of theoretical sources of critique, its psychological and sociological obstacles are the reasons for the literary and musical criticism passivity in these areas. The findings of this article indicate that the term music in "Music of Poetry" is contrary to its definition by musicologists. They also represent that the study of written compiled works of “poetry and vocal music association” can considerably help to develop and extend new prosodical perspectives in the field of literary criticism. The results of this research as an interdisciplinary study include some suggestions for identifying and increasing the mutual interests of literary and musical criticisms, the most important of which is a proposition to form study groups and hold conferences on “Criticism of Poetry and Music".